Magnetic Zeolite Composites for Heavy Metal Ions Removal: A Concise Review - Wayan Gracias; Annisha Noor Dienna; Defia Indah Permatasari (Nexus Sains dan Teknologi, 2025)
Magnetic zeolite is a composite material that combines the porous characteristics of zeolite with the magnetic separation capability of magnetic nanoparticles. This study discusses the development of magnetic zeolite synthesis using several main methods, including hydrothermal synthesis, coprecipitation, and dry-gel conversion, each offering different levels of control over particle size, surface area, and magnetic strength of the resulting composite. The synthesized materials generally possess a high surface area and strong magnetic response, making  them  effective  for adsorbing heavy metal ions from aqueous solutions. The reported maximum adsorption capacities reach 625 mg g⁻¹ for Pb(II), 204 mg g⁻¹ for Cd(II), 181 mg g⁻¹ for Cu(II), more than 400 mg g⁻¹ for Cr(VI), and around 42 mg g⁻¹ for Ni(II). According to various studies, the adsorption of heavy metal ions onto magnetic zeolite commonly follows the pseudo-second-order kinetic model and the Langmuir isotherm, indicating that the adsorption process is dominated by a monolayer chemisorption mechanism. In addition to its high adsorption capacity, the main advantage of magnetic zeolite is the ease of separating it from the solution using an external magnetic field, making it an efficient adsorbent that can be easily recovered and reused.